PENGARUH FAKTOR FUNDAMENTAL DAN FAKTOR EKONOMI MAKRO TERHADAP FLUKTUASI HARGA SAHAM PADA PERUSAHAAN YANG TERDAFTAR PADA INDEKS SAHAM SYARIAH INDONESIA DI BEI - Endah Dewi Purnamasari (Jurnal Ilmiah Ekonomi Global Masa Kini)
This research aimed to analyze the influence of fundamental and macroeconomic factors on the company's stock price fluctuations. The fundamental factor are Return On Equity (ROE), Debt to Equity Ratio (DER) and Earning Per Share (EPS). While macroeconomic factors are the currency exchange rate, inflation and interest rates.The research was conducted at the companies whose shares are included in Indonesian Sharia Stock Index (ISSI). Sampling Technique used is purposive sampling. Sampling criteria are companies whose shares are included in Indonesian Sharia Stock Index (ISSI) in period December 23, 2014 until May 2015The data used in this research is secondary data, taken from www.idx.co.id anad www.bi.go.id. Multiple Regression Analysis is used to test the data which result is Y = a + b1x1 + b2X2 + b3X3 + b4X4 + b6X6 b5X5 + e, where Y: changes in stock prices, X1: Earning Per Share (EPS), X2: Debt to Equity Ratio (DER), X3: Return On Equity (ROE), X41: the currency exchange rate, X5: inflation, X6: interest rates, a : Constants and b1, b2, b3, B41, b5, b6: Regression coefficient. Hypothesis testing via the T test and F test showed no relationship between the variables X and YThe results showed that earnings per share, debt to equity ratio, return on equity, inflation, exchange rates and interest rates have significant influence on changes in stock prices simultaneously. Based on partial t test result show that the earnings per share and a debit to equity ratio has significant influence, while the return on equity, inflation, exchange rates and interest rates do not influence the stock price changes. Key words: Fundamental factor, macro economic factor, bank stock price fluctuation